2013
DOI: 10.1080/10130950.2013.793898
|View full text |Cite
|
Sign up to set email alerts
|

Enacting masculinities: Pleasure to men and violence to women

Abstract: Feminist anthropologists have shown how women's bodies have been appropriated and rendered 'docile' by so called cultural or traditional practices, as well as by discourse. The compelled docility of African women (as that of other women in the global south), is perhaps especially visible within subtly coerced performances within a context of 'traditional' masculinised practices, such as unprotected sex, that leave many African women vulnerable and forced to negotiate a host of health concerns around sexually t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Third, we recognise that reactionary resistance to changing men and boys is often touched on, perhaps often too lightly, in several South African qualitative and ethnographic studies (e.g., Bhana and Pattman 2011 ; Langa and Kiguwa 2013 ; Naidu and Ngqila 2013 ). As such, even though it has contributed to literature and practice on gender and sexualities, the body of studies and practical interventions that focus on boys and men is confronted with encumbrances that are hard to overcome.…”
Section: Reactionary Resistance At Different Pointsmentioning
confidence: 99%
“…Third, we recognise that reactionary resistance to changing men and boys is often touched on, perhaps often too lightly, in several South African qualitative and ethnographic studies (e.g., Bhana and Pattman 2011 ; Langa and Kiguwa 2013 ; Naidu and Ngqila 2013 ). As such, even though it has contributed to literature and practice on gender and sexualities, the body of studies and practical interventions that focus on boys and men is confronted with encumbrances that are hard to overcome.…”
Section: Reactionary Resistance At Different Pointsmentioning
confidence: 99%
“…There has been a documented link between long term relationships and lack of condom use (see Naidu and Ngqila, 2013). McPhail et al (2007) also observed that at the beginning of heterosexual relationships, many couples reported condom use, which however, usually fades as the relationship progresses.…”
Section: Resultsmentioning
confidence: 98%
“…McPhail et al (2007) pointed out that this practice of vaginal douching is not associated with condom use, hence it places women at a high risk of acquiring sexually transmitted infections. Naidu and Ngqila (2013) in their study with married women, found that men who do not want to use condoms, threaten to leave their women who insist on condom use, and find other women that will have sex without condoms with them. The narratives by the circular migrant women reveal that this is no different for them.…”
Section: Such Narratives Of Constraint Are Echoed By Other Participanmentioning
confidence: 99%
“…For it is construed as especially sinful to be lesbian within the multiple contexts of the many African cultural traditions in South Africa. Thus, while there is discrimination of the lesbian community, arguably this discrimination is heightened with the African communities where particular patriarchal masculinities and prerogatives also co-exist (see Naidu and Ngqila 2013).…”
Section: Introductionmentioning
confidence: 99%